Gendered Injustice: How Prosecutor Gender Impacts Perceptions of Defendant Culpability - Stalcup, Morgan (Criminology, criminal justice, law & society, 2025)
This study investigates how prosecutor gender impacts perceptions of defendant culpability in the criminal court system. While factual guilt and evidence should determine culpability, anecdotal beliefs and research suggest that extra-legal factors, such as attorney gender, may influence legal outcomes. Past studies have shown that female attorneys may face disadvantages in negotiations, but little research has explored whether prosecutor gender affects perceptions of defendants. This issue becomes increasingly relevant as more women enter the legal profession. Using a nationwide sample of 471 American adults, this study explores three key questions: 1) whether a prosecutor’s gender influences perceptions of defendant culpability, 2) how respondent gender affects these perceptions, and 3) whether respondent gender moderates the influence of prosecutor gender. To evaluate the impact of prosecutor gender on defendant culpability, this study uses an experimental vignette design manipulating prosecutor gender. Ordered-logistic analysis shows that cases involving female prosecutors result in higher perceptions of defendant culpability relative to cases with male prosecutors. Notably, female respondents are more likely to attribute higher culpability to defendants when the prosecutor is female or when no prosecutor gender is indicated, compared to male respondents. Policy implications and future directions for research are also discussed.